SLAB FORMWORK DESIGN - Octavian George Ilinoiu (Institute of Research and Community Outreach - Petra Christian University, 2006)
Note from the Editor: In Indonesia, although cost of formwork contributes significantly to the total reinforced concrete construction cost and formwork failure will result in a very complicated construction problem, formwork design is often neglected and left to the foreman to design. This paper presents slab formwork design practice in Romania, where formwork design is a requirement to obtain professional engineer certification. This paper is a continuation of previous paper â Wall Formwork Designâ by the same author published in Dimensi Teknik Sipil, Vol. 6, no. 2, September 2004. Abstract in Bahasa Indonesia : Catatan Redaksi: Perencanaan bekisting (form work) di Indonesia sering kali dilalaikan dan diserahkan kepada pelaksana/ mandor, padahal kegagalan bekisting akan menimbulkan masalah yang sangat rumit. Bekisting juga merupakan komponen biaya pelaksanaan struktur beton bertulang yang cukup besar. Makalah ini memaparkan praktek perencanaan bekisting untuk lantai di Romania, dimana perencanaan bekisting merupakan salah satu syarat untuk mendapatkan sertifikasi insinyur professional. Makalah ini adalah kelanjutan dari makalah Wall Formwork Design, yang dimuat dalam Dimensi Teknik Sipil, Vol. 6, no.2, September 2004.